(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In this article, the main physical qualities and methods of their improvement are studied in the types of wrestling. Physical qualities, including strength, speed, endurance, flexibility and coordination, play an important role in the development of technical and tactical skills of wrestlers. The article presents the importance of each physical quality in the fight, as well as the methods and techniques used for their effective development. The importance of individual approach and regular training in the process of improvement is also emphasized. The research provides practical recommendations to improve the physical training of wrestlers and help athletes achieve better results.